Potential impact of shipping on air pollution in the Mediterranean region – a multimodel evaluation: comparison of photooxidants NO2 and O3 - L. Fink; M. Karl; V. Matthias; S. Oppo; R. Kranenburg; J. Kuenen; J. Moldanova; S. Jutterström; J.-P. Jalkanen; E. Majamäki (Atmospheric Chemistry and Physics, 2023)
Shipping has a significant share in the emissions of air pollutants such as NOx and particulate matter (PM), and the global maritime transport volumes are projected to increase further in the future. The major route for short sea shipping within Europe and the main shipping route between Europe and East Asia are found in the Mediterranean Sea. Thus, it is a highly frequented shipping area, and high levels of air pollutants with significant potential impacts from shipping emissions are observed at monitoring stations in many cities along the Mediterranean coast.